2001
DOI: 10.1002/1521-3765(20011015)7:20<4352::aid-chem4352>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Stable Three-Center Hydrogen Bonding in a Partially Rigidified Structure

Abstract: The three-center hydrogen bond in diaryl amide 1 was examined by IR and 1H NMR spectroscopy, X-ray crystallography, and ab initio calculations. By comparing 1 with its structural isomers 2, 3 and 4, and with its conformational isomers 1a-c, it was found that the two two-center components of the three-center interaction reinforce each other, that is, the enhanced stability of the three-center hydrogen bond is a result of positive cooperativity between the two components. Substituents not involved in hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
85
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 44 publications
6
85
2
1
Order By: Relevance
“…Our results indicated that the three-center hydrogen-bonding system, consisting of the S(5) and S(6) type (21) hydrogen-bonded rings, was particularly stable in the solid state and in solution (19,20). It persisted in chloroform, the highly polar dimethyl sulfoxide (DMSO), and even in water (unpublished data), and this structure was confirmed by NMR, IR, and x-ray crystallographic studies on short oligomers.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Our results indicated that the three-center hydrogen-bonding system, consisting of the S(5) and S(6) type (21) hydrogen-bonded rings, was particularly stable in the solid state and in solution (19,20). It persisted in chloroform, the highly polar dimethyl sulfoxide (DMSO), and even in water (unpublished data), and this structure was confirmed by NMR, IR, and x-ray crystallographic studies on short oligomers.…”
supporting
confidence: 66%
“…Our previous studies have demonstrated that short oligomers with m-backbones adopt a well-defined crescent conformation (12,19,20). Our results indicated that the three-center hydrogen-bonding system, consisting of the S(5) and S(6) type (21) hydrogen-bonded rings, was particularly stable in the solid state and in solution (19,20).…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…In fact there is a controversy about the energetic superiority of THB over regular or two centered HB. There are some studies that provide experimental evidence in favor, [11][12][13] however some experimental 14,15 and theoretical studies, 3 using flexible molecules as a model, provide contrary evidence.…”
Section: Introductionmentioning
confidence: 99%